Endocrine disruptors and antimicrobial agents in an intercity study in England: Towards holistic environmental and public exposure assessment using water-based epidemiology and retrospective mass spectra data mining - Eva Hawkins; Megan Robertson; John Bagnall; Barbara Kasprzyk-Hordern (Environment International)
An analytical framework was developed, allowing for suspect screening and retrospective quantification of hazardous household-derived chemicals (HDCs) in community wastewater and river water to assess public exposure and environmental health status. 11 HDCs (bisphenol A, 4 parabens, 5 antimicrobials and benzophenone-1) and 2 metabolites (bisphenol A sulfate and triclosan sulfate) were identified, confirmed and quantified in mass spectra from a multi-city study covering 5 contrasting towns and cities in England within a catchment served by 5 wastewater treatment plants (WwTPs), representing > 75 % of the whole catchment population (∼1.5 million people) and covering a 2000 km2 area. A further 5 HDC metabolites: hydroxytriclocarban,p-chlorocresol sulfate, 2,6-dimethyl-1,4-benzenediol, chloroxylenol sulfate, 2-benzyl-1,4-benzenediol were for the first time tentatively identified in wastewater and river water using suspect screening. Trends in daily loads and population normalised daily loads of HDCs were studied. Population size was identified as the key driver of environmental burden, however, impacts from industrial usage were also apparent in the case of BPA and parabens. For example, BPA population normalised daily loads indicated higher exposure estimated for communities with industrial presence indicating occupational exposure. Environmental risk assessment was also undertaken for 11 HDCs using the risk quotient (RQ) method. RQ values < 0.1, found for most HDCs in river water, suggested low risk. However, RQ values > 1 found for triclosan and triclocarban indicated potentially high risk to the environment, which is concerning due to their endocrine disruption and antimicrobial resistance properties. This study verified the potential for holistic assessment of both community and environmental exposure. It showed that different chemicals might need to be considered in the context of risks to humans and the environment (e.g., bisphenol A of high risk to humans vs triclosan and triclocarban being of high risk to the aquatic environment). Lack of analytical standards for metabolic biomarkers, as well as lack of understanding of metabolic pathways of HDCs were identified as the key limiting factors in establishing WBE as a holistic One Health tool for combined environmental and public health assessment of HDCs, especially those that are not intended for human consumption.